Implementation of Tawhid Education at State Madrasah Ibtidaiyah in Medan - Salamuddin Salamuddin; Putri Ani Dalimunthe; M Fajri Syahroni Siregar (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe learning methods and models, teacher efforts, and obstacles in teaching monotheism in madrasas. Then this study wants to find out the obstacles faced by teachers in adopting the teaching of monotheism. The research method used in this research is qualitative. Data was collected through observation, structured interviews and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results showed that the teaching methods taught in moral beliefs were speech, question and answer, discussion, practice, recitation and uswah. The teacher tries to introduce students to the teaching of monotheism in schools, such as performing the Duha prayer, reading Al-Asma-ul Husna, memorizing letters. Choose a surah, read the Qur'an 'amma' and celebrate the great Islamic important day. Supporting factors in the implementation of the teachings of monotheism by Madrasah Ibtidaiyah are high student interest in learning, good class leadership made by teachers, parental support, and community support. However, there are also obstacles, namely increasing and decreasing student interest in learning, differences in student intelligence levels, ability to manage learning, teachers, inadequate school facilities and some parents being overworked.